2014
DOI: 10.1155/2014/695387
|View full text |Cite
|
Sign up to set email alerts
|

Patch Testing in Suspected Allergic Contact Dermatitis to Cosmetics

Abstract: Background. Increasing use of cosmetics has contributed to a rise in the incidence of allergic contact dermatitis (ACD) to cosmetics. It is estimated that 1–5.4% of the population is sensitized to a cosmetic ingredient. Patch testing helps to confirm the presence of an allergy and to identify the actual allergens which are chemical mixtures of various ingredients. Objectives. The aims of this study are to perform patch testing in suspected ACD to cosmetics and to identify the most common allergen and cosmetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…21 An important finding of the present study is that the rate of patch-test positivity was significantly more with 'own hair colours' than that with PPD contained in ISS. 21 An important finding of the present study is that the rate of patch-test positivity was significantly more with 'own hair colours' than that with PPD contained in ISS.…”
Section: Discussionmentioning
confidence: 45%
“…21 An important finding of the present study is that the rate of patch-test positivity was significantly more with 'own hair colours' than that with PPD contained in ISS. 21 An important finding of the present study is that the rate of patch-test positivity was significantly more with 'own hair colours' than that with PPD contained in ISS.…”
Section: Discussionmentioning
confidence: 45%
“…Components of kumkum, applied as a cosmetic to the forehead in Asian women, commonly cause a pigmented dermatitis . The eyelids, face, and neck are the sites most frequently involved in cosmetic allergy, as observed in our study also.…”
Section: Discussionmentioning
confidence: 92%
“…Dogra et al have reported 3.2% positivity with standard cosmetic kit and 3.3% with various cosmetics out of 2065 patches applied. Kumar P et al have reported a rate of 3.75% positive reactions. Somewhat lower rate of positive reaction was observed in our study (2.12%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations